Rancang Bangun E-Learning Berbasis Website di SMK Negeri 3 Kuningan - Rafsanzani, Fajri Rafli; Ripai, Ipan (Indo-MathEdu Intellectuals Journal, 2024)
Developing an e-learning learning platform that is expected to provide easy and fast access for students and teachers in sharing subject matter, is also expected to increase the productivity of students who want to learn even outside school hours. The purpose of this study is to design and build a web-based e-learning platform at SMK Negeri 3 Kuningan which is expected to make it easier for students and teachers in learning and teaching activities. The method in this study uses the R&D method with the Rapid Application Development (RAD) model system development method. The population in this study is all teachers at SMK Negeri 3 Kuningan. The data collection technique was carried out using a lift. Data analysis was carried out on all data obtained and analyzed descriptively. The results showed that the researcher conducted a functionality test with "very feasible" results. Then the usability test was carried out by 10 teaching samples by showing a result of 87.1% which can be categorized as "very feasible". Thus, it has met the feasibility of use